2015
DOI: 10.1520/jte20140082
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cement–Sodium Silicate Grout Compounds on Void Ratio and the Coefficient of Secondary Compression of Treated Fibrous Peat

Abstract: Peats have low shear strength and high deformation characteristics. Peat is a naturally occurring material that is extremely soft with a high moisture content and exists in an unconsolidated state. The conventional binders used are cementitious materials, and the introduction of a new binder, sodium silicate, with other additives gives a better output than the conventional peat treatment. This article describes a laboratory study on the effect of different compounds of cement-sodium silicate grout on void rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Huat (2004) was indicated that cements and lime as binders, along with increasing the strength, neutralize the acidity of peat. Kazemian et al (2014) indicated that using additives such as cement, sodium silicate and kaolinite decrease the void ratio and the coefficient of secondary compression of treated fibrous peat. Moreover, the effect of three curing techniques of moist curing, air curing and moist curing with surcharge load on the strength of cement-stabilized peat was investigated in a study by Kalantari and Prasad (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Huat (2004) was indicated that cements and lime as binders, along with increasing the strength, neutralize the acidity of peat. Kazemian et al (2014) indicated that using additives such as cement, sodium silicate and kaolinite decrease the void ratio and the coefficient of secondary compression of treated fibrous peat. Moreover, the effect of three curing techniques of moist curing, air curing and moist curing with surcharge load on the strength of cement-stabilized peat was investigated in a study by Kalantari and Prasad (2014).…”
Section: Introductionmentioning
confidence: 99%
“…Huat in 2004 [2] stated that during chemical reactions initiated by stabilization, stabilizer materials such as lime or cement neutralize the acidity and through the cementation process initiated afterward, the strength properties of peat improve. Kazemian et al in 2015 [6] showed that by adding cement, sodium silicate and kaolinite as binders, the void ratio and the coefficient of secondary compression of treated fibrous peat decrease. Kalantari and Prassad [7] in a study investigated the effect of three curing techniques of moist curing, air curing and moist curing with surcharge load on the strength of cement-treated peat.…”
Section: Introductionmentioning
confidence: 99%